Homeostatic plasticity and excitation-inhibition balance: The good, the bad, and the ugly. (August 2022) - Chen, Lu; Li, Xiling; Tjia, Michelle; Thapliyal, Shruti
Abstract: In this review, we discuss the significance of the synaptic excitation/inhibition (E/I) balance in the context of homeostatic plasticity, whose primary goal is thought to maintain neuronal firing rates at a set point. We first provide an overview of the processes through which patterned input activity drives synaptic E/I tuning and maturation of circuits during development. Next, we emphasize the importance of the E/I balance at the synaptic level (homeostatic control of message reception) as a means to achieve the goal (homeostatic control of information transmission) at the network level and consider how compromised homeostatic plasticity associated with neurological diseases leads to hyperactivity, network instability, and ultimately improper information processing. Lastly, we highlight several pathological conditions related to sensory deafferentation and describe how, in some cases, homeostatic compensation without appropriate sensory inputs can result in phantom perceptions. Highlights: Hebbian and homeostatic plasticity fine-tune synaptic E/I ratio during development. Synaptic E/I balance is important for network stability and information processing. Homeostatic plasticity stabilizes neuronal firing by modification of synaptic E/I. Impaired homeostatic plasticity leads to cognitive deficits in neurological diseases. Improper homeostatic plasticity drives deafferentation-induced phantom perception.